2020
DOI: 10.4236/fns.2020.1112076
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical, Nutritional and Technological Properties of Instant Porridge Supplemented with Mung Bean

Abstract: The present study was undertaken to prepare instant porridge from some useful and available ingredients such as bulgur powder, potato, tomato, carrot, mung bean (unsoaked, soaked and germinated), then seasoned with onion, garlic, salt, black pepper, cumin and coriander to make B1, B2 and B3 formulas. Chemical, physical properties, amino acids and sensory evaluation of instant porridge formulas were determined. The data showed that B2 formula which contained soaked mung bean had the highest calories value, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…e ash contents of the three powdered porridges were similar to the three porridges developed by Mahgoub et al [53] with ash contents of 1.86 g/100 g DW, 2.01 g/100 g DW, and 2.17 g/100 g DW. e fiber contents of the three powdered porridges varied from 1.65 g/100 g DW to 2.44 g/100 g DW.…”
Section: Discussionsupporting
confidence: 78%
“…e ash contents of the three powdered porridges were similar to the three porridges developed by Mahgoub et al [53] with ash contents of 1.86 g/100 g DW, 2.01 g/100 g DW, and 2.17 g/100 g DW. e fiber contents of the three powdered porridges varied from 1.65 g/100 g DW to 2.44 g/100 g DW.…”
Section: Discussionsupporting
confidence: 78%
“…According to the survey study on eating behavior, the result interestingly demonstrated that the consumers over 65 years were being more careful to eat healthy than other younger groups (Bolek, 2021). In general, instant porridge products available in the market are usually abundant in carbohydrates but cannot supply enough protein and fat (Akonor et al, 2021;Mahgoub et al, 2020). In addition, the current research on the elderly diet has focused on the development of food ingredients, snacks, or beverages, e.g., a low-fat bologna-type meat product (Reyes-Padilla et al, 2018), a high-protein yoghurt (Kersiene et al, 2020), and a ready to drink product from Riceberry (Jaroenwanit et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The WSI determines the amount of soluble degradation from starch upon the addition of excess of water [ 27 , 53 ] and also indicates the water penetration into starch granules [ 54 ]. A lower WSI indicates minor degradation of starch [ 55 ]. The WSI values of instant porridge powders in this study, at 6.13–6.40%, were lower than reported those by Mahgoub et al (2020) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lower WSI indicates minor degradation of starch [ 55 ]. The WSI values of instant porridge powders in this study, at 6.13–6.40%, were lower than reported those by Mahgoub et al (2020) [ 55 ]. They found that WSI values of instant porridge supplemented with different types of mung bean were 16.12–22.5% [ 55 ], while a similar result was found by Walle and Moges (2017) for legume cereal blended with complementary porridge powder [ 56 ].…”
Section: Discussionmentioning
confidence: 99%